The Grotesque of Luigi Chiarelli: La maschera e il volto. - Martínez-peñuela, Ana (Cuadernos de Filología Italiana, 2003)
It deals with the way to look into the meaning of grotesque and differentiate it from humour, tragedy and satire and illustrates the coexistence of all these elements regarding grotesque. To do this I base myself on Luigi Chiarelli’s play La maschera e il volto. Grottesco in tre atti and, with the analysis of the play from a showman’s point of view (structure, space, time, items, sounds, margin notes, characters), I see the meaning of the mask how it goes towards the face to determine the individual freedom from social prejudices, which conditions his reactions.